2021
DOI: 10.3390/biomedicines10010080
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Proteome and Phosphoproteome Profiles of Rat Hippocampus after Six Months of Morphine Withdrawal: Comparison with the Forebrain Cortex

Abstract: The knowledge about proteome changes proceeding during protracted opioid withdrawal is lacking. Therefore, the aim of this work was to analyze the spectrum of altered proteins in the rat hippocampus in comparison with the forebrain cortex after 6-month morphine withdrawal. We utilized 2D electrophoretic workflow (Pro-Q® Diamond staining and Colloidal Coomassie Blue staining) which was preceded by label-free quantification (MaxLFQ). The phosphoproteomic analysis revealed six significantly altered hippocampal (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Among upregulated proteins, four of these were associated with the change in energy metabolism: electron transfer flavoprotein-ubiquinone oxidoreductase, mitochondrial ( Etfdh , ↑2.6-fold), ATPase inhibitor, mitochondrial ( Atpif ,↑2.4-fold), complex I-B17 ( Ndufb6 , ↑2.4-fold), and cytochrome c oxidase subunit 2 ( Mtco2 , ↑2.3-fold). We previously reported that the majority of altered hippocampal proteins were related to energy metabolism after both chronic morphine treatment (10–50 mg/kg, 10 days) and subsequent drug withdrawal (3 weeks, 3 months, 6 months) [ 14 , 15 , 16 ]. Volcano plots representing significantly altered proteins identified in rat hippocampus after treatment with 3 mg/kg of morphine, LYS739 , and LYS744 are depicted in Figure 2 C. Hierarchical heatmap clustering of all identified protein expression profiles in rat hippocampus is presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among upregulated proteins, four of these were associated with the change in energy metabolism: electron transfer flavoprotein-ubiquinone oxidoreductase, mitochondrial ( Etfdh , ↑2.6-fold), ATPase inhibitor, mitochondrial ( Atpif ,↑2.4-fold), complex I-B17 ( Ndufb6 , ↑2.4-fold), and cytochrome c oxidase subunit 2 ( Mtco2 , ↑2.3-fold). We previously reported that the majority of altered hippocampal proteins were related to energy metabolism after both chronic morphine treatment (10–50 mg/kg, 10 days) and subsequent drug withdrawal (3 weeks, 3 months, 6 months) [ 14 , 15 , 16 ]. Volcano plots representing significantly altered proteins identified in rat hippocampus after treatment with 3 mg/kg of morphine, LYS739 , and LYS744 are depicted in Figure 2 C. Hierarchical heatmap clustering of all identified protein expression profiles in rat hippocampus is presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Rat brain cortex and hippocampus were selected as a part of the central nervous system; rat spleen lymphocytes represented the peripheral region. Our previous data showed the opposite effect of morphine treatment and withdrawal on proteome changes in cortical and hippocampal samples [ 13 , 14 , 15 , 16 ]. Label-free quantification (MaxLFQ) was used for all proteomic analyses [ 13 , 14 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DEPs were assessed for protein–protein interaction (PPI) analysis using STRING (11.0) web server. , The PPI network was performed at a high confidence level of 0.700 allowing all active interaction sources including direct (physical) and indirect (functional) associations. The evidence of these predicted interactions is presented via genomic context, coexpression, prior knowledge, and high-throughput experiments.…”
Section: Methodsmentioning
confidence: 99%
“…An overactive incentive-motivational system centered in ventral tegmental area ( VTA ) dopamine ( DA ) neurons and its neural projections to the nucleus accumbens ( NAc ) serves as the “accelerator” (reward, persistent drug-induced behaviors) ( Figure 1 ). Subregions of the prefrontal cortex ( PFC ) play both direct and subtle regulatory roles as a “behavioral brake” over drug use (inhibitory control, executive function) and is vulnerable to disruption by chronic opioid exposure leading to heightened preoccupation and anticipation of drug acquisition ( Ujcikova et al, 2021 ; Ceceli et al, 2023 ). A well-characterized role for the 5-HT 2A R in meso-corticolimbic neurocircuitry serves to illustrate the power and complexity of this system ( Figure 1 ).…”
Section: The 5-ht 2a R As a Target For Opioid Use ...mentioning
confidence: 99%